What motivates and inhibits Indian textile firms to embrace sustainability? - Anupriya Sharma; Sapna A. Narula (Asian Journal of Sustainability and Social Responsibility (AJSSR), 2020)
Our study identifies the motivations and barriers to pursue sustainability for textile firms in India and the impact of these factors on firm's adoption of sustainable business practices. Our study is based on primary survey of 113 managers from textile firm who are responsible for taking decisions towards formulation of business policies, and drivers are the reasons why companies decide to pursue sustainable practices. Regression analysis shows that regulatory, market and economic factors are more significant in pushing firms to adopt sustainable practices, whereas initial cost of compliance is the biggest challenge in implementing these practices. The results of the study are extremely important in assisting firm managers in enhancing their understanding of factors for a successful environmental strategy and influencing them to embrace sustainability. The study also contributes to our understanding of environmental issues in textile supply chain and how it could be made environmentally more sustainable. Finally, implications to extend research on role of internal actors in the organisation in shaping and implementing environmental strategies are presented.
Keywords: 650; Responsible business; Sustainability; Drivers; Barriers; Indian textile industry; Managerial perception